Prevalence of clinical and radiographic signs of osteoarthrosis of the temporomandibular joint in an older persons community - Schmitter, Marc; Essig, Marco; Seneadza, Sophia Viktoria Adzoa; Balke, Zibandeh; Schröder, Johannes; Rammelsberg, Peter (Dentomaxillofacial radiology, 2010)
The aim was to assess the prevalence of osteoarthrosis (OA) in the temporomandibular joint (TMJ) in a sample of older people by use of contrast agent-enhanced MRI.
Online veröffentlicht am 28. Januar 2014
Gesehen am 15.06.2023